Description of the nymphs of Nehalennia integricollis Calvert and N. pallidula Calvert (Odonata: Coenagrionidae) - Tennessen, K. J. (Zootaxa, 2026)
The final instars of Nehalennia integricollis Calvert and Nehalennia pallidula Calvert are described in detail and illustrated based on specimens from Florida and Texas. Nehalennia integricollis has only 1 prominent seta on each side of the prementum, same as the sympatric N. gracilis Morse and N. irene (Hagen); it differs from both those species by 1) proximal portion of epiproct and paraprocts darker than the distal part vs. not darker, and 2) posterolateral corners of head with 3–6 small spinules with dark bases vs. 10 or more spinules with dark bases or 3–6 spinules with pale bases. Nehalennia pallidula resembles N. minuta (Selys) in possessing 3 or 4 prominent setae on each side of the prementum; it differs in having a slightly larger prementum (length 1.70–2.05 mm vs. 1.60–1.65 mm, width 1.43–1.58 mm vs. 1.35–1.40 mm). Further diagnostic notes to distinguish the nymphs of the five New World species of Nehalennia are provided.